ANALYSIS OF THE TRACKING INITIATIVES OF COLORECTAL CANCER IN BRAZIL - Camila Mendes TOLEDO; Letícia Maria Perrelli Ramalho de ALMEIDA; Marcelo AVERBACH; Joanny de Lima e Silva BARBOSA (Arquivos de Gastroenterologia, 2023)
ABSTRACT Background: Colorectal cancer (CRC) is an important public health problem, as it represents the world’s third most diagnosed neoplasm and the fourth cause of mortality. Its prevention can be divided into primary, secondary, demonstrated by tracking techniques, and tertiary, which consists of cancer diagnosis in symptomatic patients. Despite presenting a high incidence, the mortality rates decreased in the past two decades in developed countries, while the opposite happened in underdeveloped countries. That is attributed to the increase of colorectal cancer tracking programs in developed countries, which allows the precocious diagnosis and treatment of precancerous injuries and CRC. In that manner, the American Cancer Society divides the secondary tracking methods in exams based on feces samples and visual analysis of the colon and rectum, indicating its initiation starting at 45 years old in lower-risk patients. Objective: Verify in an analytical way the actions of colorectal cancer tracking held in Brazil, as to evaluate the necessity of implementation of a national tracking program of CRC. Methods: The methodology was based on a descriptive-quantitative secondary study that correlated the incidence of CRC, its morbidity and mortality, and the impact of the precocious tracking programs. It included activities not reported in medical literature through personal contacts with coordinators of regional programs to compare with the existent data in the literature. It was used as a variable for the tracking strategies the exams held, and their respective results. Results: It described nine programs held in different regions in Brazil, using two screening methods for CRC: a noninvasive method that consists of the research of blood hidden in feces, being the majority through the FIT method, and an invasive method, having the colonoscopy as its representant. These initiatives were effective in the detection of early forms of this disease. Conclusion: Despite the existence of several private tracking programs and the broad divulgation of the importance of the tracking and the early diagnosis of colorectal cancer, it was demonstrated that Brazil lacks a national program that patronizes the tracking methods, which reflects in the major prevalence of late diagnosis in the population.